New interaction solutions for the (3+1)-dimensional Jimbo–Miwa equation. (1st November 2018) - He, Chunhua; Tang, Yaning; Ma, Jinli
Abstract: In this paper, based on the Hirota bilinear form and a "rational-cosh-cos" type test function, we will study new interaction solutions among the lump waves, kinky waves and periodic waves for the (3+1)-dimensional Jimbo–Miwa equation. We analyze the dynamic behaviors of the constructed solutions in four special cases in detail. And the dynamic characteristics of the obtained solutions are illustrated by some interesting figures with the help of Maple.